Relationship between prognostic score and thyrotropin receptor (TSH-R) in papillary thyroid carcinoma: immunohistochemical detection of TSH-R. - Tanaka, K. (Nature Publishing Group, 1997)
We have demonstrated the expression of thyrotropin receptor (TSH-R) in thyroid neoplasms (13 adenomas, 21 papillary carcinomas, two follicular carcinomas) and adjacent normal thyroid using the monoclonal antibody against human TSH-R and have also demonstrated a relationship between prognostic scores and the expression of TSH-R. Among the adenomas, eight showed an intensity similar to that of normal thyroid and five showed a higher intensity than normal. Two tumours exhibited heterogeneous distribution of TSH-R. Among the papillary carcinomas, seven showed similar intensity to normal tissue and four showed higher intensity and ten showed weaker intensity. Eight tumours showed heterogeneous distribution of the stain. Among the follicular carcinomas, one showed similar intensity to normal tissue and the other exhibited weaker intensity. Both cases showed homogeneous distribution of TSH-R. The adenomas never showed a weaker intensity than normal thyroid, but various intensities of TSH-R occurred in differentiated carcinomas. There was no significant relationship between the clinical data and the signal intensity in the adenomas. Among the papillary carcinomas, however, the group with weaker intensity had significantly poorer prognostic scores than the other two groups. Thus, we assume that low TSH-R may be expressed by the clinically high-risk group of patients with papillary thyroid carcinoma. IMAGES: